Giant cell myocarditis: evidence for the macrophage origin of the giant cells. - Theaker, J M (1985)
In order to elucidate the origin of giant cells in giant cell myocarditis a case has been studied immunohistologically using monoclonal antibodies against a variety of antigens, including those associated with muscle and macrophages. The results strongly suggest that the giant cells are derived from macrophages rather than the muscle cells.